Interactions between K-carrageenan and chitosan in nanolayered coatings - Structural and transport properties - Pinheiro, A. C. (2012)
The interactions between -carrageenan and chitosan, two oppositely charged polysaccharides, have been investigated through microcalorimetric and quartz crystal microbalance measurements. Microcalorimetric measurements show that -carrageenan/chitosan interaction is an exothermic process and that the alternate deposition of -carrageenan and chitosan results in the formation of a nanolayered coating mainly due to the electrostatic interactions existing between the two polyelectrolytes (though other types of interactions may also be involved). Quartz crystal microbalance measurements confirmed that the alternating deposition of -carrageenan and chitosan resulted in the formation of a stable multilayer structure. The -carrageenan/chitosan nanolayered coating, assembled on a polyethylene terephthalate (PET) support, was characterized in terms of its surface (contact angle measurements) and gas barrier properties (water vapor and O2 permeabilities) and analyzed by scanning electron microscopy (SEM). The water vapor permeability (WVP) and the oxygen permeability (O2P) of the -carrageenan/chitosan nanolayers were found to be 0.020 ± 0.002 × 10−11 and 0.043 ± 0.027 × 10−14 g m−1 s−1 Pa−1, respectively. These results contribute to a better understanding of the type of interactions that play role during the construction of this type of nanostructures. This knowledge can be used in the establishment of an approach to produce edible, biodegradable multilayered nanostructures with improved mechanical and barrier properties for application in, e.g. food and biomedical industries.